2012
DOI: 10.1016/j.canlet.2012.02.035
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1/CXCR4 signaling induces pancreatic cancer cell invasion and epithelial–mesenchymal transition in vitro through non-canonical activation of Hedgehog pathway

Abstract: In our previous study, we found that blockade of SDF-1/CXCR4 signaling inhibits pancreatic cancer cell migration and invasion in vitro. However, the mechanism governing the downstream regulation of SDF-1/CXCR4-mediated invasion remains unclear. Here we report the role of SDF-1/CXCR4 in pancreatic cancer and the possible mechanism of SDF-1/CXCR4-mediated pancreatic cancer invasion. We show that there is a cross-talk between SDF-1/CXCR4 axis and non-canonical Hedgehog (Hh) pathway in pancreatic cancer. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 28 publications
7
125
1
Order By: Relevance
“…Hedgehog pathway is necessary not only for maintenance of the stem cell compartment, but also for the induction of metastasis and regulation of EMT (22,27). Recently published data suggest that inhibition of the CXCR4/CXCL12 signaling pathway may also downregulate the hedgehog pathway (28). However, consistent with previous studies (29), we found that AMD3100 treatment did not result in inhibition of the hedgehog pathway in CSCs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Hedgehog pathway is necessary not only for maintenance of the stem cell compartment, but also for the induction of metastasis and regulation of EMT (22,27). Recently published data suggest that inhibition of the CXCR4/CXCL12 signaling pathway may also downregulate the hedgehog pathway (28). However, consistent with previous studies (29), we found that AMD3100 treatment did not result in inhibition of the hedgehog pathway in CSCs (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 89%
“…pancreatic cancer EMT through the activation of the Hedgehog pathway (31). The present study demonstrated that in the CXCR4 siRNA group of cells, the expression of N-cadherin and MMP2/9 were attenuated, while E-cadherin was upregulated, and the same results were observed in xenograft models.…”
supporting
confidence: 79%
“…Proteins of the Hedgehog (Hh) signaling pathway, an important regulator of human embryonic development, are highly expressed in pancreatic cancer tissues or cells, and their expression appears to correlate to the occurrence, development and biological behavior of tumor cells (4). Hh signaling activation is a common event in pancreatic cancer (5).…”
Section: Introductionmentioning
confidence: 99%